2002
DOI: 10.1046/j.1365-2052.2002.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

MHC‐DRB exon 2 allele polymorphism in Indian river buffalo (Bubalus bubalis)

Abstract: The polymorphism of the major histocompatibility complex (MHC) class II DRB gene of riverine buffalo (Bubalus bubalis) was studied. Second exon sequences from the buffalo DRB locus, homologous to the cattle DRB3 gene, were amplified and characterized. A combination of single strand conformation polymorphism (SSCP) and heteroduplex analysis (HA) in a non-denaturing gel was used to identify new DRB second exon sequences. SSCP, HA and finally sequencing allowed the identification of 22 MHC-DRB exon 2 alleles from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Previous work in Bubalus bubalis defined 8 DRB alleles among 75 animals from different buffalo populations in different countries [20], while a study of 25 unrelated Indian river buffalo revealed 22 DRB alleles [21]. These data, together with the present study, demonstrate that allelic frequencies of BoLA-DRB3 appear to depend on the breed and population, likely a result of founder population structure and selection pressure.…”
Section: Discussionsupporting
confidence: 62%
“…Previous work in Bubalus bubalis defined 8 DRB alleles among 75 animals from different buffalo populations in different countries [20], while a study of 25 unrelated Indian river buffalo revealed 22 DRB alleles [21]. These data, together with the present study, demonstrate that allelic frequencies of BoLA-DRB3 appear to depend on the breed and population, likely a result of founder population structure and selection pressure.…”
Section: Discussionsupporting
confidence: 62%
“…These PBRs under strong positive selection might be because of it responsible for antigen recognition. In other Ruminantia, positive selection also appeared almost in these PBR sites, especially in Asian buffalo (Bubalusbubalis) (De et al, 2002), African buffalo (Synceruscaffer) (Wenink et al, 1998), Moose (A. alces) (Mikko et al, 1999). However, South African antelope (Damaliscus pygargus pygargus) had the considerable number of positive selection sites in Non-PBRs (4) and PBRs (12) (Schaschl et al, 2004).…”
Section: Selection On Mobe-drbmentioning
confidence: 86%
“…For comparative sequence analysis, we included our previously reported MHC-DRB Exon II sequences of zebu cattle (AF261953-AF261954, AF272862–AF272876, AF272878–AF272882) and buffalo (AF3854473–AF385480, AF261955-AF261956, AF270653–AF270659, AF270661–AF270673) [14, 16]. Besides, other reported BoLA-DRB3 sequences from official BoLA web page (http://www.projects.roslin.ac.uk/bola/bolahome.html, http://www.ebi.ac.uk/cgi-bin/ipd/mhc/view_nomenclature.cgi?bola.drb3) and DRB sequences from other ruminant species like sheep ( Ovis aries , AF126432–AF126441, Y10245–Y10249, U00204–U00219, U00221–U00225, U00227–U00237), goat ( Capra hircus ; AB008347–AB008362), big horn sheep ( Ovis canadensis ; AF324–AF324861), white-tailed deer ( Odocoileus virginianus ; AF082161–AF082175), and red deer ( Cervus elaphus ; U11101–U11108, U11110–U11116, U11118–U11119, U11121, U11212, U11213, and U11215–U11218) were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to other ruminant species, buffalo MHC locus has been less extensively studied. MHC gene complex of buffalo has been mapped on chromosome 2 [13] but very few reports are available on their nature of diversity [14, 15]. Indian Zebu cattle and buffaloes are well adapted to tropical climate and are resistant to many common infectious diseases.…”
Section: Introductionmentioning
confidence: 99%